EEG analysis during salat and act-out salat / Mohammad Javad Safari - Mohammad Javad, Safari (2012)
Salat is a specific worship in Islam and consists of body movement and recitation of some religious phrases. This report presents the analysis changes in mean gamma (25-60 Hz) power during performing Salat and act-out Salat in five normal subjects (age between 20 and 29 years old). During Salat, electroencephalography (EEG) record were obtained from eight main regions of scalp (F3, F4, C3, C4, P3, P4, O1 and O2). Power spectral density (PSD) of the signal in each position was computed by using Welch’s method because, in this method, variance of the random process decreases in comparison to basic periodogram. The comparison of mean gamma power between Salat and act-out Salat indicated that during different positions of Salat praying, gamma powers are higher than act-out praying. Parametric statistical analyses (Paired sample t-test) results indicated during standing and bowing positions mean gamma power of Salat had significant differences with act-out praying. During prostrating position, the significant differences of gamma power were at frontal, parietal and occipital regions. In sitting position the gamma power was significant at parietal region. Investigation of all channels showed that changes of parietal channels were significant in all positions. The results of this study revealed that during performing Salat mean gamma power in the left hemisphere is higher than right side. Previous studies shows that left part of the brain interact more with parasympathetic nervous activity and the right part is related to sympathetic system. These results proved that performing Salat improves parasympathetic nervous activity it means that concentration provides significant relaxation for prayers mind.